El enfoque sociocultural del lenguaje: más allá de lo lingüístico y lo comunicativo - Pérez Guzmán, Jesús (Enunciación, 2022)
In recent decades, in the global field of education, a view that understands the teaching of reading and writing as practices –also called the sociocultural approach– has been gaining strength. In this sense, this article presents a document review in light of the following questions: What are the emphases in the teaching of reading and writing that occupy a preponderant place in Colombian schools and what are their usual practices? How is a sociocultural approach different from those other approaches? What elements does a sociocultural view take from linguistics and communication? Accordingly, qualitative research is carried out via the document analysis method based on the following stages: 1) search and selection of information and 2) information analysis. As a result, it is found that the approaches with the greatest tradition in schools are the linguistic and the communicative ones; the teaching of reading from a sociocultural perspective goes beyond what these two perspectives propose; and, although the sociocultural approach differs from the linguistic and communicative ones, it takes up elements from these to offer a broader view. Finally, it is indicated that the teaching of reading and writing as practices is the most pertinent perspective in the context of Colombian basic and secondary education.